Enabling the uptake of livestock-water productivity interventions in the crop-livestock systems of sub-Saharan Africa - Amede, Tilahun; Geheb, Kim; Douthwaite, Boru (Commonwealth Scientific and Industrial Research Organisation, 2009)
Livestock–water productivity (LWP) refers to a set of innovations that could contribute towards reducing the amount of water needed per unit of output generated. But what does it take to get these ideas adopted by livestock keepers in crop–livestock systems? In this paper, we treat LWP as an innovation, and consider in what ways it may be introduced and/or developed among the crop–livestock agricultural systems by drawing on successful examples of change. In the first part of this paper, we introduce relevant tenets of the innovation systems literature, and introduce a three-component conceptual framework for the adoption of LWP technologies. In the second part, we describe three successful cases of resources use change. In the final section, we identify what we consider to be necessary components in successful change, and relate these to LWP. We argue that, in the under-regulated crop–livestock systems of eastern Africa, key areas for focus include social institutions, political systems, gender and leadership.